The Transcendence of The Worship of Ratu Hyang Tumuwuh Behind a Series of Sesolahan Rêjang Kuno Pura Luhur Batukau - Widiantari, Ni Wayan; Yasa, I Wayan Suka; Winaja, I Wayan (IJCAS (International Journal of Creative and Arts Studies), 2025)
This article presents the results of a cultural reflection conducted over the past four years (October 2021 to early 2025) through research on Sesolahan Rêjang Kuno at Pura Luhur Batukau. Employing the epoche phase of Husserlian phenomenological methodology alongside the sahådaya–sahådayasamvàda approach derived from the Nāṭyaśāstra's rasa theory, qualitative data were systematically collected, analyzed, and validated through triangulation techniques. The study identifies factors facilitating transcendental experiences, outlines the processes by which transcendence occurs, examines its psychological impact on the dancers, and explores the theological frameworks of the supporting community and the cosmological context of Pura Luhur Batukau. Findings indicate that this transcendental potential remains largely unrecognized by both dancers and the community, as the performance of the Rêjang dance tends to be oriented primarily toward fulfilling ceremonial completeness (jangkep). This study therefore serves not only as a source of insight but also as a proposed solution for enhancing collective energy toward transcendence. More broadly, it offers a framework for the revitalization of ancient Sesolahan traditions in other regions and provides conceptual inspiration for the development of modern agricultural technologies grounded in traditional and even ancient agrarian civilizations, such as that flourishing on the southern slopes of Mount Batukau. Transendensi Pemujaan Ratu Hyang Tumuwuh di Balik Rangkaian Sesolahan Rêjang Kuno Pura Luhur Batukau Abstrak Artikel ini merupakan hasil refleksi budaya setelah empat tahun terakhir (Oktober 2021, sampai awal 2025) melakukan penelitian terhadap Sesolahan Rêjang Kuno Pura Luhur Batukau. Didukung penerapan tahapan epoche teori fenomenologi Husserlian dan metode sahådaya-sahådayasamvàda teori rasa Nāṭyaśāstra, diperoleh data-data kualitatif yang di analisis secara verstehen, kemudian diuji validitasnya melalui trianggulasi data berdasarkan waktu dan sumber data. Kesimpulan bermakna menarasikan tentang; faktor-faktor pendukung terjadinya transendensi, proses terjadinya, berikut dampak transendensi terhadap kondisi psikologis penari, prinsip teologis masyarakat pendukungnya, dan kondisi kosmologis Pura Luhur Batukau. Selama ini potensi tersebut belum disadari sepenuhnya oleh para penari maupun masyarakat pendukungnya, sehingga pelaksanaan setiap Rêjang lebih terkonsentrasi pada tuntas atau ‘jangkep’nya upacara. Oleh sebab itu, temuan ini menjadi informasi sekaligus solusi bagi peningkatan energi kolektif atas proses transendensi. Pada ruang lingkup lebih luas, dapat memotivasi pelestarian Sesolahan kuno di daerah lain, juga inspirasi bagi perkembangan teknologi agraris moderen berbasis peradaban agraris tradisional bahkan kuno, seperti peradaban agraris pegunungan di lereng selatan Gunung Batukau.